DEFINING THE PHYSICAL ACTIVITY ENVIRONMENT IN PRIMARY SCHOOLS ACROSS NORTH MACEDONIA: COSI STUDY - Mihajlova, Katerina; Wallace, Silver Lorraine; Stamenova, Aleksandra; Spiroski, Igor (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2025)
Encouraging children to engage in physical activity (PA) is crucial for their overall development. The school environment can play a significant role in shaping children‘s PA habits, which in turn can positively impact their overall health and wellbeing. The aim of this study was to describe characteristics of the PA environment in primary schools across North Macedonia using data from the World Health Organization’s European Childhood Obesity Surveillance Initiative (COSI)—6th round. Materials and Methods: A primary school representative (n=111) responded to questions regarding the PA environment, which included questions about having outdoor and indoor playgrounds and gymnasiums, using of outdoor playgrounds outside of the school hours and during unfavorable weather conditions and organizing PA in and outside of the school hours. Descriptive statistics were conducted to depict the PA environment in primary schools across North Macedonia. Results: Most primary schools had an outdoor playground (94.6%), provided ≥2 hours per week of physical education lessons (89.2%), and had an indoor gymnasium (83.8%). However, smaller primary schools (≤29 pupils) were significantly less likely to have an indoor gymnasium. Approximately half of the primary schools (48.5%) offered organized sport/physical activities ≥1 time per week outside of school hours. Outside of school hours, most primary schools permitted the use of outdoor play areas (77.1%). Conclusion: In conclusion, while the overall PA environments were positive, all Macedonian primary schools did not possess adequate recreational facilities and space for students to be engaged in regular PA. Thus, there is a pressing need for collaborative efforts among schools, local and national authorities to address this issue effectively, aiming to combat childhood obesity and promote increased PA among young students
Keywords: primary schools; children; physical activity; physical activity environment; COSI